Analysis of Tear Ferning Patterns in Young Female Subjects with Refractive Errors - Mana A. Alanazi; Gamal A. El-Hiti; Alaa Al-Madani; Raied Fagehi (Journal of Ophthalmology)
To evaluate the dry eye symptoms and ocular tear film in young female subjects with refractive errors (RE) using the ocular surface disease index (OSDI), phenol red thread (PRT) and tear ferning (TF) tests. Methods. A group of 50 young female subjects (mean ± standard division = 20.3 ± 1.1 years) with RE (−0.25 to −6.00D) completed the study. An age-matched control group consisting of 50 healthy normal eye female subjects (22.2 ± 1.5 years) was recruited for comparison. The OSDI was completed first, followed by PRT and TF tests. Results. Median OSDI and TF scores were significantly higher (Mann–Whitney test; P<0.001) among the study group subjects [median (interquartile range (IQR)) = 13.5 (15.3) and 1.6 (1.3), respectively] compared to the control group [6.0 (4.0) and 0.9 (0.8), respectively], whereas the median PRT score was significantly lower (Mann–Whitney test; P=0.003) in the study group [(27.5 (6.3) mm] compared to the control group [29.5 (5.0) mm]. For subjects within the mild RE group (N = 30), significant differences (Mann–Whitney test, P<0.001 to 0.005) were found between the median OSDI, PRT, and TF scores and those recorded within the control group. For the subjects with moderate RE (N = 20), significant differences (Mann–Whitney test, P<0.001 to 0.002) were found between the median OSDI and TF scores, and those recorded within the control group. Conclusion. The presence of RE in young females has a negative effect on tear film in terms of dry eye symptoms, tear volume, and TF grades. Dry eye symptoms experienced by subjects with RE and the TF grades were significantly higher compared with the control group. In addition, the tear volume was significantly lower in the study group. Clearly, RE has a risk factor for dry eye.